PENGARUH PEMAHAMAN PERATURAN PAJAK, SANKSI PAJAK, DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - RIANA RUSETIAWATI (UNIVERSITAS PEMBNAGUNAN NASIONAL VETERAN JAKARTA, 2021)
This research is a quantitative method research that aims to determine the effect of understanding tax regulations, tax sanctions, and taxpayer awareness on individual taxpayer compliance. The theory of planned behavior applied in this research explains that the behavior of taxpayers is based on the perception that behavioral control has a direct or indirect influence (through intention) on behavior. The method used to collect the sample is accidental sampling. The population consists of 11,661 registered taxpayers at KPP Pratama Jakarta Kebayoran Baru Dua in 2020. The sample consists of 90 respondents. This research uses primary data as a source of data under study, namely data obtained from questionnaires. This research uses the Structural Equation Model (SEM) method using the Smart Partial Least Square (PLS) version 3.0 application. This research shows that the variable understanding of tax regulations has an effect on individual taxpayer compliance, while the variables of tax sanctions and taxpayer awareness have no effect. Keywords: Understanding Tax Regulations, Tax Sanctions, and Awareness of Taxpayers on Individual Taxpayer Compliance.